The Concept of Character Education Based on Marhamah in Tafsir Al-Azhar by Buya Hamka - Yusuf, Erick; Hafidhuddin, Didin; Husaini, Adian; Nur, Muh. Arbiyansyah (Journal of Islamic Studies and Education, 2024)
The main problem raised in this jurnal is how the concept of marhamah described by Buya Hamka can be implemented in the current education system to produce individuals who are not only intellectually intelligent but also have noble character in accordance with the goals of national education based on the 1945 Constitution. Then there is still high behavior that is not in accordance with character education regulations such as bullying, use of illegal drugs, alcohol and the rampant promiscuity, sexual harassment, brawls and violence, as well as current phenomena such as excessive anxiety (Anxiety), mental health (mental health) and even the impact of causing a rampant suicide (suicide) among teenagers and the latest is online gambling addiction. In addition, the challenge in character education today is how to integrate spiritual and moral values effectively in the formal education process because the concept of Character Education is not yet comprehensive and optimal in its application. The research method used is a literature review (Library research) and text analysis, with the main focus on the Tafsir Al-Azhar as the main source. The results of the study show that Buya Hamka emphasizes the importance of integrating the values of affection in character formation and not only limited to individual behavior, but is a moral foundation that must be applied in community and state life. This finding shows that the concept of character education based on marhamah in Tafsir Al-Azhar is relevant to be implemented in a modern education system.